2006
DOI: 10.1097/01.mpa.0000202945.78331.93
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Islets Through Expansion and Differentiation of Non-islet Pancreatic Cells Discarded (Pancreatic Discard) After Islet Isolation

Abstract: Using the specified culture methods, non-islet pancreas cells can generate cell clusters resembling islets. These ICCs, obtained from fractions of the pancreas that are otherwise discarded, continue to differentiate after transplantation to become mature islets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Whether in the native pancreas they reside in the islet or the exocrine tissue will be unknown until a specific marker has been identified. Since this work was published a number of groups have repeated and confirmed that a such a precursor cell exists in both rodent and human (Seeberger et al, 2006;Todorov et al, 2006) pancreata. One study would seem to corroborate the work by Dor and colleagues as it showed that human insulin-positive cells undergo an epithelial to mesenchymal transition when kept in culture (Gershengorn et al, 2004).…”
Section: Islet Neogenesis: the Current Hypothesesmentioning
confidence: 86%
“…Whether in the native pancreas they reside in the islet or the exocrine tissue will be unknown until a specific marker has been identified. Since this work was published a number of groups have repeated and confirmed that a such a precursor cell exists in both rodent and human (Seeberger et al, 2006;Todorov et al, 2006) pancreata. One study would seem to corroborate the work by Dor and colleagues as it showed that human insulin-positive cells undergo an epithelial to mesenchymal transition when kept in culture (Gershengorn et al, 2004).…”
Section: Islet Neogenesis: the Current Hypothesesmentioning
confidence: 86%
“…Previous studies have generated functional islets from islet cells themselves (Gershengorn et al 2004, Russ et al 2008, Joglekar et al 2009a as well as exocrine and duct cells from adult human pancreas (Bonner-Weir et al 2000, Todorov et al 2006) from either cadavers or living organ donors. Indeed, bone marrow stem cells can also be subcultured in vitro to more passages, but reduced levels of functional cells were obtained (Wu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although generation of functional neoislets has been reported from various adult human pancreatic tissues, including pancreatic islets (Lechner et al 2005), nonislet pancreatic cells, discarded after islet isolation (Todorov et al 2006), and exocrine cells (Rapoport et al 2009), it remains to be determined whether these sources provide the amount of neoislets required for in vivo regeneration therapy for diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…To test if the interaction with VECs would enhance endocrinal differentiation in vitro, we co-cultured the VECs and NEECs to form a spherical tissue complex in a suspension culture, the method previously used for generating islet-like tissues and known to increase their insulin-secretion ability [27,28]. Cells dissociated from culture containers were swirl-incubated in a culture medium to promote direct homotypic and heterotypic cell-to-cell contacts.…”
Section: Discussionmentioning
confidence: 99%